Family Finances and Debt Overhang: Evolving Consumption Patterns of Spanish Households - Hector Sala; Pedro Trivín (Institute of Labor Economics (IZA), 2022)
This paper studies the direct impact of households' debt on consumption over the business cycle. We use household-level panel data for Spain, and focus on a interesting period of analysis, 2002-2017, characterized by large variations in leverage, consumption, and asset prices. We find that debt levels exert a negative impact on consumption, which is particularly strong in periods of high leverage and falling asset prices. This negative effect is persistent in time and significant along the post-Great Recession deleveraging process of Spanish households. We further observe that: (i) changes in households' debt in past periods are not relevant in determining consumption; (ii) households adjust faster their consumption to debt that is non-related to real estate assets; (iii) results are not driven by the characteristics of real estate loans; and (iv) credit constraints do not play a major role in shaping the debt-consumption nexus. We conclude that, in contrast to the spending normalization hypothesis, it is debt overhang what is likely to prevail in a situation of high leverage and financial stress such as the one brought by the Great Recession. Consequently, policies preventing households to embark in excessive leverage in good times and debt relief policies in bad times have a role to play to avoid larger consumption decreases in recessive periods.
Keywords: D12; D14; E21; G01; G51; 330; consumption; household debt; financial stress; debt overhang; survey